One-pot synthesis of gold nanoparticle/molybdenum cluster/graphene oxide nanocomposite and its photocatalytic activity - Barras, Alexandre; Das, Manash R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Cordier, Stephane; Szunerits, Sabine; Boukherroub, Rabah (Applied Catalysis B-Environmental, 2013)
The paper reports on a facile one-pot synthesis of a tri-component gold nanoparticle/molybdenum cluster/graphene oxide (AuNPs@Mo-GO) nanohybrid composite. The synthetic methodology consists on direct UV irradiation of an aqueous solution containing graphene oxide (GO), Na-2[Mo6Br8(N-3)(6)], HAuCl4 center dot 3H(2)O and isopropanol at room temperature in air using a UV fiber lamp. The composite material exhibits very high photocatalytic activity for the degradation of rhodamine B under visible light irradation. The resulting nanohybrid material was characterized using Raman spectroscopy, UV-vis spectrometry, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). (c) 2012 Elsevier B.V. All rights reserved.
Keywords: gold nanoparticles; graphene oxide; Nanohybrid; Photodegradation; Rhodamine B; visible light; [Mo6Br8(N-3)(6)](2-)cluster